Gambaran Pengetahuan Keluarga Tentang Cara Merawat Pasien Halusinasi Di Rumah - Lendra - Hayati; Veny - Elita; Oswati - Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study is to describe a family of knowledge about how to care for patients with hallucination at home. The design used is simple descriptive. This research is conducted at the clinic at Tampan Mental Hospital with 30 respondents. Measuring instrument used is a questionnaire that has been tested for validity and the reliability.. The result shows that the majority of respondents as many as 21 people (70%.) Have good level of knowledge. It is expected to nurse at Tampan Mental Hospital Riau Province, to give health education about hallucinations more frequent whichis useful to increase family knowledge about the hallucinations, as well as the patient's family can be motivate to control patients to the hospital on a regular basis. Keywords : Hallucinations, Families, Knowledge